Effect of Resveratrol and Tiron on the Inactivation of Glyceraldehyde-3- phosphate Dehydrogenase Induced by Superoxide Anion Radical - Rodacka, A.; Strumillo, J.; Serafin, E.; Puchala, M. (Current Medicinal Chemistry, 2014)
Protein damage mediated by oxidation has been associated with aging and age-related diseases, in particular neurodegenerative diseases. The protein that is known to be one of the major targets of oxidative stress is glyceraldehyde- 3-phosphate dehydrogenase. GAPDH is believed to play a key role in certain neurodegenerative disorders, such as Alzheimer’s, Parkinson’s, and Huntington’s diseases. Several recent studies have suggested that a wide range of variety of polyphenols including resveratrol may have neuroprotective effects. Here, we present data that clearly indicate the prooxidative properties of resveratrol and tiron in the inactivation of GAPDH induced by the superoxide anion generated via xanthine oxidase mediated oxidation of xanthine. Generated in the studied system tiron and resveratrol radicals are much more efficient in the inactivation of GAPDH than the superoxide anion alone. The analysis of CD spectra of protein exposed to the tiron and resveratrol radicals revealed little effect on the secondary structure of GAPDH. In both cases reduction of α-helical structure was followed by the increase in β-sheet conformation. Thus, the most probable mechanism of inactivation of GAPDH in the studied system is oxidation of cysteine residues in the catalytic center of the enzyme. Finally, molecular modeling of the resveratrol - GAPDH and tiron - GAPDH complexes showed potential binding sites for those antioxidants with binding affinity -45 kcal/mol and -48 kcal/mol respectively.
Keywords: antioxidant